(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Cricoid pressure (CP), established by Brian Sellick in 1961, is a method employed to avert regurgitation and aspiration during endotracheal intubation. It is commonly employed in emergency procedures, where the danger of aspiration is increased due to full stomach conditions. Although commonly employed during rapid sequence induction and intubation, the effectiveness and appropriate implementation of CP remain contentious issues. Objectives: To assess the knowledge, attitudes, practices, and adherence rates of anesthesiologists regarding cricoid pressure application during rapid sequence induction in emergency settings at tertiary care hospitals in Karachi, Sindh, Pakistan. Method A cross-sectional study was undertaken at The Indus Hospital, Aga Khan Hospital, Civil Hospital, JPMC, LNH, SIUT, Patel Hospital, and Abbasi Shaheed Hospital in Karachi over a six-month period from June 23, 2023, to December 23, 2023. A total of 85 anaesthesiologists were included in the present study. The questionnaire comprises three primary sections: knowledge of cricoid pressure, attitudes, and a final component addressing attitudes. Results: The mean age of the patients was 30.73 ± 4.59 years. Merely 25% of participants accurately identified the anatomical position of the cricoid cartilage. Approximately 99% recognised that cricoid pressure is utilised to avert stomach aspiration during the induction of anaesthesia. Moreover, around 86% of individuals indicated that they acquired information predominantly through clinical practice. Conclusion: In conclusion, our findings underscore the necessity for focused educational initiatives, standardised training programs, and continuous professional development to guarantee a uniform and evidence-based application of cricoid pressure in peri-operative care.